2017
DOI: 10.3892/etm.2017.4109
|View full text |Cite
|
Sign up to set email alerts
|

Anti-climacterium effects of pomegranate concentrated solutions in ovariectomized ddY mice

Abstract: Abstract. In the present study, the complex anti-climacterium potential of standardized pomegranate concentrated solution (PCS) was investigated using bilateral ovariectomy (OVX) female ddY mice. Changes in body weight and gain during experimental periods, food consumption, serum estradiol levels, total body and abdominal fat densities, abdominal fat pads, and uterus weights were observed, along with the histopathology of abdominal fat pads and uterus for anti-obesity and estrogenic effects. In addition, liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Studies have shown that OVX rats experience a reduction in serum oestrogen levels (Kang et al. 2017 ). In accordance with other studies, we discovered that the serum oestrogen level in model group rats was significantly lower than that in rats in the sham-operated group, and that FAEE treatment led to a marked increase in the serum oestrogen level compared with that in the model group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that OVX rats experience a reduction in serum oestrogen levels (Kang et al. 2017 ). In accordance with other studies, we discovered that the serum oestrogen level in model group rats was significantly lower than that in rats in the sham-operated group, and that FAEE treatment led to a marked increase in the serum oestrogen level compared with that in the model group.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, estrogen regulates insulin sensitivity of the insulin-sensitive organs, including the liver, pancreas, and white adipose tissue, and thermogenesis in brown adipose tissue, in addition to affecting lipid metabolism [7,29]. Thus, estrogen deficiency increased triglyceride levels in insulin resistance, leading to increased visceral fat storage and imbalance between HDL and LDL cholesterol [9]. In postmenopausal women, estrogen deficiency may be an important obesity-triggering factor [40].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, estrogen regulates insulin sensitivity of the insulin-sensitive organs, including liver, pancreas, white adipose tissue, and thermogenesis in brown adipose tissue, in addition to affecting lipid metabolism [8]. Thus, 2 of 15 a deficiency of estrogen leads to increased visceral fat storage, an imbalance between high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol levels, and increased triglyceride levels, resulting in insulin resistance [9,10]. Osteoporosis is a systemic metabolic phenomenon that frequently occurs in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Sex hormones influence body fat distribution and adipocyte differentiation. Some researchers have reported that an estrogen deficiency may be an important obesity-triggering factor [ 44 ], and several studies have reported that estrogen deficiency increases the body weight of mice [ 45 , 46 , 47 ]. In the present study, we showed that the administration of TSG effectively inhibited weight gain by estrogen deficiency.…”
Section: Discussionmentioning
confidence: 99%